Effectiveness of conservation areas for protecting biodiversity and ecosystem services: a multi-criteria approach. Issue 1 (1st January 2017) - García Márquez, Jaime Ricardo; Krueger, Tobias; Páez, Carlos Andrés; Ruiz-Agudelo, César Augusto; Bejarano, Patricia; Muto, Tito; Arjona, Fabio
ABSTRACT: In land planning strategies, methods to quantify ecosystem services (ESs) are now used to complement biodiversity assessments. Tension arises when areas important for biodiversity do not spatially co-occur with important areas for ESs. We investigate the effectiveness of protected areas in simultaneously protecting biodiversity and ESs in central Colombia and identify complementary areas. We map, integrate using a multi-criteria technique and correlate five indicators (sensitive species, ecological systems, habitat quality, scenic beauty and water provision). Reflecting the uncertainty in criteria weights, multiple maps were created and overlain with current protected areas to investigate their effectiveness. A consensus and an uncertainty map were calculated to identify multifunctional areas (high value for biodiversity and high provision of ESs and low uncertainty). Protected areas show low to intermediate levels of effectiveness (3–56% percentage overlap with simulated areas), with water provision being the service least effectively protected. Indicators do not show high levels of correlation (all p  < 0.57). Sensitive species are negatively correlated with all other indicators. High representativeness levels were found around the city of Bogotá; still, extensive multifunctional areas are not contemplated under any protection status. We advocate the use of our approach to identify multi-purpose areas that are robust to divergent stakeholder opinions.EDITED BY Berta Martin-Lopez